(untitled) (Research, Society and Development, 2020)
Intimate partner violence (IPV) is configured as any form of violent behavior committed both at home and in any intimate relationship of affection, regardless of cohabitation, which can impact the psychological health of people who are affected. Therefore, this study sought to evaluate the evidence on the prevalence of depression in people who experienced violence by intimate partners through a systematic review with meta-analysis. Searches were carried out in the PubMed, LILACS, SciELO and Virtual Health Library databases. Fifteen articles were included and it was possible to identify that the prevalences were varied, with minimum rates of 5.7% up to a maximum of 79.4%. It was concluded that according to the added value, there is a positive correlation so that the occurrence of violence by intimate partners can generate the occurrence of depression. The review therefore indicates the need for preventive and health promotion actions, especially with regard to mental health.